Comparison of Risk Management in Non-profit Banks and Financial Institutions versus Other Conventional Banks and Financial Institutions in Iran - Museloo, Khalil Abbasi; Toraj, Noormohammd (International Journal of Economics and Financial Issues, 2017)
This present study has been done to compare risk management differences in banks and interest-free loan financial institutes with other conventional banks and financial institutes of Iran. This study is descriptive-comparative and cross-sectional in terms of time criteria (longitudinal - cross sectional). The questionnaire by Javadi and Qouchifard (2009), which translated and validated by researcher, was used to collect data. Population consisted of all banks, interest-free loan financial institutes and other conventional and financial institutes of Iran. Due to limited number of population (100 institutes and banks), it was divided in two groups (banks and interest-free loan financial institutes) as samples. Research results based on U Mann-Whitney Test showed that there were remarkable differences in using credit risk management, capital investment on stocks and liquidity risk management in banks, interest-free loan financial institutes and other conventional banks and financial institutes. But there were no significant differences in using market risk management, return risk rate, and methods of operational risk management in banks, interest-free loan financial institutes and other conventional banks and financial institutes of Iran. Keywords: Risk Management, Banks, Interest-free Loan Financial Institutes JEL Classifications: E37, E32